(untitled) (Fiep Bulletin - online, 2016)
This article seeks to present aspects related to popular culture in Brazilian territory and its influence on a community, a fact that leads one social group to present its identity with certain folk frolics. And this perspective we discuss the relations between the races represented by ox-Bumba in Parintins, municipality in the state of Amazonas, which through its representations and melodies tell the life of mestizo and indigenous legends pegged the região.E this regard we point the importance Brazilian culture to the educational space, highlighting the discipline of Physical Education and its playful aspect. Aiming at promoting Brazilian cultural wealth, in order to show what advocates the National Curricular Parameters -Themes Cross and Physical Education, pointing to school as a multicultural space, where they fit in the curriculum themes of popular cultural slant